Development of e-menu web service integrated with payment gateway using SOA method (Case Study: Angkringan Ateng) - Risandi, Arfika Putri; W.S, Sanggita Erinne; Almas, Nayaka Nadhiftya; Afriansyah, Enri Hilmy; Marpaung, Andreas Adiputra (Jurnal Mandiri IT, 2024)
This research discusses the development of an e-menu web service integrated with a payment gateway using the Service-Oriented Architecture (SOA) approach at Angkringan Ateng. This technology allows customers to view menus, order, and pay online, improving efficiency and quality of service. The SOA method was chosen for its flexibility and scalability in the development of complex systems, making it easy to integrate and maintain services independently. This study includes requirements analysis, architecture design, implementation, and system evaluation. The results show that the developed e-menu system is able to improve operations and customer experience, and can serve as a model for the development of similar applications in other culinary industries.